A STUDY ON THE STUDENTS’ ABILITY IN IDENTIFYING MORAL LESSON OF NARRATIVE TEXT AT GRADE VIII OF MTS. PP. TUNAS HARAPAN TEMBILAHAN - Julia Citra; Maria Olpa (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2017)
The purpose of this research are to know the students’ ability in identifying moral lesson of narrative text at grade VIII of Mts. PP. Tunas Harapan Tembilahan. The research design was Descriptive research. The population of this research was 68 students and the sample also was 68 students. The technique of taking the sample in this research was total sampling because the population less than 100 students. To get the data of students’ ability in identifying moral lesson of narrative text, the researcher gave identifying moral lesson of narrative text test to 68 students. Before giving the test to the sample, the researcher did the validity test in the other school in order to get the valid questions. The researcher did the validity test at grade VIII MTs. Nurul Jihad Tembilahan Hulu, there were 17 students who answered the validity test, and from the validity test the researcher got 7 questions that is not valid. The test asked about moral lesson from the character in narrative text and the moral lesson of narrative text. The result of the test showed that there were 9 students (13%) were classified as having good, 55 students (81%) were classified as having enough, and 4 students (6%) were classified as having poor. So, the researcher finds that the mean of student’s score was 53,5, and it was categorized Enough. So, the researcher can conclude that the students less comprehend in identifying moral lesson of narrative text, it showed from the percentage result where the students who having good score only 13%. It because identifying moral lesson of narrative text is not easy, the students must comprehend before to indentifying moral lesson of narrative text.